An appraisal of Milgrom’s fitting formula by the antigraviton-graviton theory - WONG, Wing-hong; WONG, Wing-to; WONG, Wing-keung; WONG, Ling-mei (International Journal of Advanced Astronomy, 2014)
On one hand, the Wong’s antigraviton-graviton theory (AGT), which may also be called a new quantum gravity theory, predicts that at the limit of infinite radius, the effective acceleration is proportional to the square root of the Newtonian gravitational acceleration. Thus it partially supports Milgrom’s fitting formula (MIFF). On the other hand, our AGT discovers that the definition of the critical acceleration as a universal parameter by MIFF is not adequately valid. Keywords: Cosmology: Theory, Dark Matter, Galaxies: Kinematics And Dynamics, Gravitation, Large-Scale Structure Of Universe.